Ozone in food processing - O'Donnell, C. (Wiley-Blackwell, 2012)
This book is the first to bring together essential information on the application of ozone in food processing, providing an insight into the current state-of-the-art and reviewing established and emerging applications in food processing, preservation and waste management.